Awareness of the Consumption of Dietary Supplements among Students in a University in Saudi Arabia - Jozaa Z. AlTamimi (Journal of Nutrition and Metabolism)
The dietary supplement market in Saudi Arabia is growing alongside the number of Saudis consuming dietary supplements. It is therefore increasingly important for healthcare personnel to understand the consumption rate of dietary supplements, whether they are used wisely, and the know-how concerning their use and dosage. The purpose of this study was to clarify the overall awareness of dietary supplement consumption among female students of Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia. Using a descriptive approach, data were collected from 759 female students (mean age = 22.1 ± 1.7 years) via an electronic survey. All participants reported having consumed dietary supplements at some point, and 32.3% were taking them at the time of the survey. They took supplements primarily for aesthetic reasons (e.g., hair and skin health) and preferred purchasing supplements at pharmacies. Nearly all (89.9%) participants could define supplements correctly, and 43.6% reported that supplements improved health. More than half the sample believed that supplements are safe. While a large proportion of participants correctly identified the recommended number of daily servings of fruits and vegetables, relatively few actually consumed that recommended amount. More than one-third of participants consumed more than one type of supplement simultaneously, and more than half reported that they would use supplements when necessary in the future. The results of this study suggest a need for long-term studies on the consumption of nutritional supplements among Saudis and its impact on health.